PEMBERDAYAAN MASYARAKAT DALAM PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA MELALUI PRODUKSI ECO ENZYM DI KELURAHAN LAMBUNG BUKIT KOTA PADANG - Firdani, Fea; Putri, Ananda Rada; Saputra, Doni; Panjaitan, Mira Lilia Dei Br; Salbila, Putri Aurani; Sasy, Syahiro Regusti De (Jurnal Hilirisasi IPTEKS, 2025)
Waste that is not managed correctly can pollute the environment, endanger public health, and increase the risk of flooding, especially in flood-prone areas such as Batu Busuk Village, Lambung Bukit Village, Padang City. Organic waste processing through the manufacture of eco-enzymes is an alternative environmentally friendly solution that the community can carry out independently. This activity aims to improve community knowledge and skills in managing organic waste through training in making eco-enzymes to reduce the risk of waste accumulation and flooding. This activity method uses a participatory approach involving the community through counseling, discussions, and direct practice of making eco-enzymes. The activity was carried out in November 2024. Knowledge evaluation was carried out through pre-tests and post-tests, with statistical analysis to measure the effectiveness of the activity. The statistical test results showed a significant increase in community knowledge after the counseling activity, with a p-value of 0.001. The community could also practice making eco-enzymes independently, producing environmentally friendly products from household organic waste. In conclusion, this activity has increased community knowledge and skills in managing organic waste. Sustainable eco-enzyme production can reduce waste volume, prevent accumulation, and reduce the risk of flooding and environmental pollution. Therefore, local governments are advised to support eco-enzyme training, provide supporting facilities, and integrate community-based waste management into environmental management policies.